2018
DOI: 10.5194/acp-18-14493-2018
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric oxidation in the presence of clouds during the Deep Convective Clouds and Chemistry (DC3) study

Abstract: Abstract. Deep convective clouds are critically important to the distribution of atmospheric constituents throughout the troposphere but are difficult environments to study. The Deep Convective Clouds and Chemistry (DC3) study in 2012 provided the environment, platforms, and instrumentation to test oxidation chemistry around deep convective clouds and their impacts downwind. Measurements on the NASA DC-8 aircraft included those of the radicals hydroxyl (OH) and hydroperoxyl (HO2), OH reactivity, and more than … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 69 publications
(87 reference statements)
4
27
0
Order By: Relevance
“…The 21 June 2012 DC3 case of a decaying MCS provided measurements of the chemical composition of the dissipating anvil region and convective outflow of the MCS over an 11-hr period during daytime. During the morning period (the first 5 hr of measurements), ozone increased by~12 ppbv (Brune et al, 2018), consistent with observed HO 2 and box model calculations, and another 8 ppbv (20 ppbv in total) by midafternoon . Results from these two case studies are in the upper end of the range reported by previous studies.…”
Section: Chemistry In Convective Outflowssupporting
confidence: 82%
See 1 more Smart Citation
“…The 21 June 2012 DC3 case of a decaying MCS provided measurements of the chemical composition of the dissipating anvil region and convective outflow of the MCS over an 11-hr period during daytime. During the morning period (the first 5 hr of measurements), ozone increased by~12 ppbv (Brune et al, 2018), consistent with observed HO 2 and box model calculations, and another 8 ppbv (20 ppbv in total) by midafternoon . Results from these two case studies are in the upper end of the range reported by previous studies.…”
Section: Chemistry In Convective Outflowssupporting
confidence: 82%
“…Using the WRF‐Chem model at convective parameterization scales, Li et al () found that wet scavenging overestimated removal of these soluble trace gases, but the predicted scavenging efficiency improved compared to observations when ice retention fractions for each trace gas were included in the parameterization. In general, observations in the upper troposphere outflow regions found that formaldehyde had the highest mixing ratios of these three HO x precursors and was calculated to be the dominant HO x precursor for ozone formation downwind of the storms (Brune et al, ).…”
Section: Findings From Dc3mentioning
confidence: 99%
“…In contrast to the PBL where both positive and negative model discrepancies occur, aloft in the FT the model exhibits a large negative bias for both VOC-carbon (-64%) and reactivity (-63%) that manifests essentially everywhere. Such a severe discrepancy has implications for our understanding of FT HOx cycling (Brune et al, 2018;Mao et al, 2009), ozone production at higher altitudes where its climatic effects are strongest (Apel et al, 2015;Bertram et al, 2007), and possibly, secondary organic aerosol loading (Bianchi et al, 2016;Cappa, 2016;Kirkby et al, 2016;Trostl et al, 2016;Heald et al, 2005). We explore potential causes for these observed discrepancies in Sec 6.1.…”
Section: Accuracy Of Ctm-predicted Voc-carbon and Reactivitymentioning
confidence: 91%
“…In contrast to the PBL where both positive and negative model discrepancies occur, aloft in the FT the model exhibits a large negative bias for both VOC carbon (−64 %) and reactivity (−63 %) that manifests essentially everywhere. Such a severe discrepancy has implications for our understanding of FT HO x cycling (Brune et al, 2018;Mao et al, 2009), ozone production at higher altitudes where its climatic effects are strongest (Apel et al, 2015;Bertram et al, 2007), and possibly secondary organic aerosol loading Cappa, 2016;Kirkby et al, 2016;Heald et al, 2005). We explore potential causes for these observed discrepancies in Sect.…”
Section: Accuracy Of Ctm-predicted Voc Carbon and Reactivitymentioning
confidence: 99%